1999
DOI: 10.1099/0022-1317-80-3-571
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and glial cell type-specific promoters within adenovirus recombinants restrict the expression of the apoptosis-inducing molecule Fas ligand to predetermined brain cell types, and abolish peripheral liver toxicity.

Abstract: Gene therapy using Fas ligand (FasL) for treatment of tumours and protection of transplant rejection is hampered because of the systemic toxicity of FasL. In the present study, recombinant replication-defective adenovirus vectors (RAds) encoding FasL under the control of either the neuronal-specific neuronal-specific enolase (NSE) promoter or the astrocyte-specific glial fibrillary acidic protein (GFAP) promoter have been constructed. The cell type-specific expression of FasL in both neurons and glial cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 67 publications
1
51
0
Order By: Relevance
“…We have also previously demonstrated that the GFAP promoter driving transgenes encoded within recombinant adenovirus vectors exerts a several fold lower translational activity when compared to the hCMV promoter. 35 To test the therapeutic effects of adenovirus-mediated decorin gene therapy in our brain tumor model, 3 days after the implantation of tumor cells, adenovirus vectors bearing the therapeutic gene were stereotactically injected into the tumor. The intratumoral delivery of 4 Â 10 7 iu of RAd/GFAP/decorin and RAd/hCMV/decorin resulted in no significant difference in the survival of CNS-1 tumorbearing rats as compared with RAd/hCMV/b-gal-injected animals (data not shown).…”
Section: Decorin Overexpression For Glioma Treatmentmentioning
confidence: 99%
“…We have also previously demonstrated that the GFAP promoter driving transgenes encoded within recombinant adenovirus vectors exerts a several fold lower translational activity when compared to the hCMV promoter. 35 To test the therapeutic effects of adenovirus-mediated decorin gene therapy in our brain tumor model, 3 days after the implantation of tumor cells, adenovirus vectors bearing the therapeutic gene were stereotactically injected into the tumor. The intratumoral delivery of 4 Â 10 7 iu of RAd/GFAP/decorin and RAd/hCMV/decorin resulted in no significant difference in the survival of CNS-1 tumorbearing rats as compared with RAd/hCMV/b-gal-injected animals (data not shown).…”
Section: Decorin Overexpression For Glioma Treatmentmentioning
confidence: 99%
“…9 Thus, the results obtained after infection of HepG2 hepatocellular carcinoma cells by Adgfa2TK are of particular interest. After infection with Adgfa2TK, this cell line showed no sensitivity to up to 50 g/mL GCV, whereas infection with AdCMVTK resulted in 80% toxicity after exposure to 50 g/mL GCV.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several recent studies have in fact demonstrated that a GFAP promoter fragment can induce specific expression of a transgene in glial cells compared with non-glial cells (neuroblastoma, fibroblast, epithelial cell line) and can limit expression of a toxic protein in glial cells after systemic administration. 8,9 In this study, we investigated the use of a 2.2-kb human GFAP promoter fragment, gfa2, to target HSV-TK expression in gliomas using a high-titer recombinant adenovirus. The gfa2 promoter was selected for use as it has previously been shown to effectively express genes specifically in astrocytes, 10 including expression of HSV-TK in cultured glioma cells 11 and in astrocytes in transgenic mice.…”
mentioning
confidence: 99%
“…Cells were prepared for FACS analysis as described previously. 28 Secretion of mFasL into the culture supernatants was also verified. To prepare the supernatants, the culture medium was centrifuged at 200Âg for 10 minutes to remove any apoptotic cells.…”
Section: Fas Ligand Expression and Induction Of Apoptosismentioning
confidence: 94%
“…The construction of RAds expressing Escherichia coligalactosidase (RAd35 ), 24,25 HSV1 -TK ( RAd128 ) , 15,26 and mFasL ( RAdhCMV-mFasL ), 27,28 all under the control of the major immediate early human cytomegalovirus promoter ( mIE -hCMV ) , has been described in detail previously. The RAds were grown and purified as previously described.…”
Section: Recombinant Adenovirusesmentioning
confidence: 99%